BRASSINAZOLE RESISTANT 1 Mediates Brassinosteroid-Induced Calvin Cycle to Promote Photosynthesis in Tomato - Yin, Xiaowei; Tang, Mingjia; Xia, Xiaojian; Yu, Jingquan (Frontiers in Plant Science, 2022)
Calvin cycle is a sequence of enzymatic reactions that assimilate atmospheric CO2 in photosynthesis. Multiple components are known to participate in the induction or suppression of the Calvin cycle but the mechanism of its regulation by phytohormones is still unclear. Brassinosteroids (BRs) are steroid phytohormones that promote photosynthesis and crop yields. In this study, we study the role of BRs in regulating Calvin cycle genes to further understand the regulation of the Calvin cycle by phytohormones in tomatoes. BRs and their signal effector BRASSINAZOLE RESISTANT 1 (BZR1) can enhance the Calvin cycle activity and improve the photosynthetic ability. BRs increased the accumulation of dephosphorylated form of BZR1 by 94% and induced an 88–126% increase in the transcription of key genes in Calvin cycle FBA1, RCA1, FBP5, and PGK1. BZR1 activated the transcription of these Calvin cycle genes by directly binding to their promoters. Moreover, silencing these Calvin cycle genes impaired 24-epibrassinolide (EBR)-induced enhancement of photosynthetic rate, the quantum efficiency of PSII, and Vc,max and Jmax. Taken together, these results strongly suggest that BRs regulate the Calvin cycle in a BZR1-dependent manner in tomatoes. BRs that mediate coordinated regulation of photosynthetic genes are potential targets for increasing crop yields.